Penanganan Keterlambatan Stok Obat Di Klinik GKB - Devy Ana Choirun Nisa; Wati, Hernum Daya (Universitas Muhammadiyah Gresik, 2025)
Abstract Background – Timely drug availability is an important element in health care, especially in primary care facilities such as clinics. Objective – This study aims to identify the factors that cause delays in drug stock and formulate an effective handling strategy at GKB Clinic. Design / Methodology / Approach – The research method used is descriptive quantitative research with a survey approach and correlational data analysis. Findings – The results showed that delays in drug stocks were caused by several main factors, namely a slow procurement process, lack of drug needs planning, limited logistics information systems, and delivery constraints from central distributors. To overcome this, it is recommended to implement an integrated e-logistics system, increase the capacity of human resources in planning drug needs, and periodically evaluate the procurement and distribution process. Proper handling is expected to improve the efficiency of the drug supply chain and the quality of health services at the clinic. Research Implication – This study demonstrates the importance of improving the logistics and drug procurement systems at GKB Clinic. Practically, the findings may encourage management to implement an integrated logistics information system and improve staff competency in stock planning. Theoretically, these results enrich the study of pharmaceutical supply chain management in primary care facilities. In addition, these findings can also be taken into consideration in formulating more efficient drug distribution policies, especially in remote areas. Limitations – The study was limited to one location, Klinik GKB, so the results cannot be generalized. The data used is qualitative and dependent on respondents' perceptions, and does not include a comprehensive cost or logistics efficiency analysis. Keyword: Drug Stock Delay, Logistics Management, Drug Procurement, Pharmaceutical Supply Chain.